The Role of Mothers in Maintaining Oral Health and The Dental Hygiene of Children - Yolanda Oktavia; Harsismanto J; Hendry Boy; Mira Sri Gumilar; Elisa Fitriana Handayani (Jurnal Keperawatan Silampari, 2026)
This study aimed to determine the relationship between mothers' roles in maintaining oral health and children's dental hygiene at Melati Kindergarten and Mutiara Umi Kindergarten, Pematang Tiga District. This study was analytical with a cross-sectional approach. The results showed that mothers' roles in maintaining oral health were mostly less than 74.3%. Children's dental hygiene at Melati Kindergarten and Mutiara Umi Kindergarten, Pematang Tiga District, as measured by the PHP-M index, was mostly in the moderate category, at 45.7%. In conclusion, there is a significant relationship between mothers' roles in maintaining oral health and children's dental hygiene at Melati Kindergarten and Mutiara Umi Kindergarten, Pematang Tiga District. Keywords: Preschool Children, Dental Hygiene, Mother's Role